Integrating family planning into Ethiopian voluntary testing and counselling programmes - Duff Gillespie; Heather Bradley; Metiku Woldegiorgis; Aklilu Kidanu; Sabrina Karklins
PROBLEM: Governments and donors encourage the integration of family planning into voluntary testing and counselling (VCT) services. We aimed to determine if clients of VCT services have a need for and will accept quality family planning services. APPROACH: "Voluntary HIV counselling and testing integrated with contraceptive services" is a proof-of-concept study that interviewed 4019 VCT clients before the addition of family planning services and 4027 different clients after family planning services were introduced. Clients attended eight public VCT facilities in the Oromia region, Ethiopia. The intervention had four components: development of family planning counselling messages for VCT clients, VCT provider training, contraceptive supply provision and monitoring. LOCAL SETTING: Ethiopia's population of 80 million is increasing rapidly at an annual rate of 2.5%. Contraceptive prevalence is only 15%. The estimated adult HIV prevalence rate is 2.1%, with more than 1.1 million people infected. The number of VCT facilities increased from 23 in 2001 to more than 1000 in 2007, and the number of HIV tests taken doubled from 1.7 million tests in 2007 to 3.5 million in 2008. RELEVANT CHANGES: Clients interviewed after the introduction of family planning services received significantly more family planning counselling and accepted significantly more contraceptives than those clients served before the intervention. However, three-quarters of the clients were not sexually active. Of those clients who were sexually active, 70% were using contraceptives. LESSONS LEARNED: The study demonstrated that family planning can be integrated into VCT clinics. However, policy-makers and programme managers should carefully consider the characteristics and reproductive health needs of target populations when making decisions about service integration.